Anthropometric Profile of Latin American Population: Results From the ELANS Study - Herrera-Cuenca, Marianella; Kovalskys, Irina; Gerardi, Alejandro; Hernandez, Pablo; Sifontes, Yaritza; Gómez, Georgina; Yépez García, Martha Cecilia; Méndez-Pérez, Betty; Landaeta-Jimenez, Maritza; Pareja, Rossina; Cortés, Lilia Yadira; Rigotti, Attilio; et al. (Frontiers in Nutrition, 2021)
Background: Latin America has experienced changes in lifestyle since 1960. Aim: The aim was to determine the prevalence of obesity and stunting among eight countries of Latin American and to identify determinant risk factors for obesity. Subjects and methods: Data were obtained from 9,218 participants of the Latin American Study of Nutrition and Health (ELANS), a multicenter cross-sectional study of representative samples in eight Latin American countries. All participants completed a standard protocol to investigate nutrient intake, and anthropometric variables (weight, height, and circumferences), analyzed by country, gender, age and socio-economic status. Results: The prevalence of obesity was higher in Costa Rica and Venezuela (29%) and lower in Colombia (16%), stunting was reported higher in Peru (47%) and lower in Argentina (17%), waist and neck circumferences showed higher values in Costa Rica (43%) and Chile (52%) and lower values in Colombia (23% and 26%). Conclusion: This study indicates a trend toward increasing overweight and obesity that is associated with lower socio-economic status, being a woman and concur with inadequate intakes of calcium which may be related to poor quality diet and in the long term could constitute risk factors for chronic diseases and a health burden to the region.